1981
DOI: 10.1073/pnas.78.6.3378
|View full text |Cite
|
Sign up to set email alerts
|

Control region for adenovirus VA RNA transcription.

Abstract: Plasmids containing the VA RNA genes of adenovirus are faithfully transcribed by a crude cytoplasmic extract containing DNA-dependent RNApolymerase II [Wu, G.-J. (1978) Proc. NatI. Acad. Sci. USA 75, 2175USA 75, -2179. By subjecting these DNA templates to in vitro site-directed mutagenesis with a novel enzyme of Pseudomonas and recloning in pBR322, we have constructed an ordered series of deletions which affect the in vitro transcription of the major RNA polymerase III viral product, VA, RNA. Three regions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 37 publications
2
58
0
Order By: Relevance
“…However, the upstream start site may be positioned by an 11 mer, the GAGAGGGCTGG sequence, that spans the start of the first repeat (Fig. IA) and which has significant homology with the Pol III A box promoter consensus sequence (20,21,(30)(31)(32)47). Alternatively, initiation site selection by Pol III may depend on the 5' flanking sequence, as previously shown for tRNA genes (40,41).…”
Section: Cell-free Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the upstream start site may be positioned by an 11 mer, the GAGAGGGCTGG sequence, that spans the start of the first repeat (Fig. IA) and which has significant homology with the Pol III A box promoter consensus sequence (20,21,(30)(31)(32)47). Alternatively, initiation site selection by Pol III may depend on the 5' flanking sequence, as previously shown for tRNA genes (40,41).…”
Section: Cell-free Transcriptionmentioning
confidence: 99%
“…The human Alu-repeat clones, pPD8 and pPD6, were kindly provided by Drs. T. Friedmann and P. Deininger; adenovirus VA1-5'A55 DNA was a generous gift of Dr. R. Weinmann (5,21). Plasmid DNAs were purified by banding in CsCl gradients (22,23).…”
mentioning
confidence: 99%
“…These results suggest that an increased quantity of Earlier workers have shown that the VAI gene is a strong competitor for transcription of VAII gene (9,10) presumably competing for initiation factors. Deletion mapping studies demonstrated that only nucleotide sequences from +54 to +69 of VAI promoter are capable of competing for transcription with a second VAI gene in vitro (10). The mechanism of initiation of transcription of class III genes is being investigated intensely in several laboratories.…”
Section: Construction Of Mutant Virusesmentioning
confidence: 99%
“…the VAI gene competing strongly with the VAII gene for one or more transcriptional factors, thus limiting the transcription of VAII gene (13). In in vitro transcription assays, DNA sequences from +54 to +69 of VAI gene promoter are capable of competing for transcription with another VAI gene or VAII gene (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation